Inorganic Halide Perovskite Solar Cells: Progress and Challenges - Tian, Jingjing; Xue, Qifan; Yao, Qin; Li, Ning; Brabec, Christoph J.; Yip, Hin‐Lap (Advanced energy materials, 2020)
All‐inorganic perovskite semiconductors have recently drawn increasing attention owing to their outstanding thermal stability. Although all‐inorganic perovskite solar cells (PSCs) have achieved significant progress in recent years, they still fall behind their prototype organic–inorganic counterparts owing to severe energy losses. Therefore, there is considerable interest in further improving the performance of all‐inorganic PSCs by synergic optimization of perovskite films and device interfaces. This review article provides an overview of recent progress in inorganic PSCs in terms of lead‐based and lead‐free composition. The physical properties of all‐inorganic perovskite semiconductors as well as the hole/electron transporting materials are discussed to unveil the important role of composition engineering and interface modification. Finally, a discussion of the prospects and challenges for all‐inorganic PSCs in the near future is presented. Recent progress in inorganic lead‐based and lead‐free CsBX3 perovskite solar cells using various strategies is reviewed and their prospects and challenges in the future are discussed in detail.